Pengaruh Metode Pembelajaran Dan Minat Belajar Mahasiswa Terhadap Hasil Belajar Manajemen Konstruksi - Rifana S.I Kawet (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2017)
The purpose of this study is learning about learning and learning. This research method is method by designing treatment based on level 2x2. The data analysis technique used (anava) two lines, then continued with Tuckey test. The results of that study; there are differences in learning outcomes between students using reciprocal learning methods and students using discussion learning methods; there is an interaction between learning and student interest in learning; student learning outcomes using reciprocal learning methods are higher than students using discussion learning methods in students with a high learning interest; student learning outcomes using reciprocal learning methods are lower than students using discussion learning methods in students with low learning interest.